Field Reaction of some Jute (Corchorus spp.) Varieties to Yellow Mite, Polyphagotarsonemus Latus Banks - Rahman, Sahidur; Khan, Matiyar Rahaman (Asian Journal of Biological and Life Sciences, 2012)
Field reaction of eight popular jute varieties of West Bengal, India viz. JRO-524, JRO-632, JRO-878, JRO-7835, JRC-212, JRC-321, JRC-4444 and JRC-7447 was observed against yellow mite, Polyphagotarsonemus latus Banks. Among the olitorius varieties, JRO¬7835 was found to be tolerant to yellow mite with minimum 7.82 % leaf infestation. Minimum number of mites per leaf was also recorded to be 13.22 in this variety. The variety JRO-632 was found to be the moderately susceptible with 10.90 % leaf infestation and 18.99 numbers of mites per leaf. On the other hand, the capsularis varieties were found resistant to yellow mite with incidence range from 4.96% leaf infestation with 6.90 numbers of mites per leaf in var.JRC-4444 to 6.91% leaf infestation with 10.91 numbers of mites per leaf in the var. JRC-212. Correlation studies of the plant characteristics of different jute varieties with the incidence of yellow mite revealed that plant height, number of leaves per plant, leaf area and moisture content of leaves had positive significant effect on the incidence of the pest. However, leaf thickness and chlorophyll content of leaves had no effect on the incidence of yellow mite.